2005
DOI: 10.1002/tox.20120
|View full text |Cite
|
Sign up to set email alerts
|

Organ distribution and bioaccumulation of microcystins in freshwater fish at different trophic levels from the eutrophic Lake Chaohu, China

Abstract: This article reports the organ distribution and bioaccumulation of hepatotoxic microcystins (MCs) in freshwater fishes at different trophic levels from the large, shallow, eutrophic Lake Chaohu in September 2003, when there were heavy surface blooms of toxic cyanobacteria. Among all fish, intestines and blood had the highest average content of MC-RR + MC-LR (22.0 and 14.5 microg g(-1) DW, respectively), followed by liver, bile, and kidney (7.77, 6.32, and 5.81 microg g(-1) DW, respectively), whereas muscle had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
4
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 264 publications
(167 citation statements)
references
References 15 publications
8
153
4
2
Order By: Relevance
“…This result is consistent with previous studies (Chen et al, 2006;Zhang et al, 2009), which indicate that accumulation in the intestinal wall can inhibit further transport of MCs into internal organs. The MC concentrations in the livers of the four fish species studied here were all relatively low, which contradicts the results of previous studies (Kankaanpää et al, 2005;Li et al, 2004;Malbrouck et al, 2003;Xie et al, 2005). The liver is an important detoxification organ, and bile plays an important role in the elimination and recirculation of excess MCs from the fish liver (Tencalla and Dietrich, 1997).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This result is consistent with previous studies (Chen et al, 2006;Zhang et al, 2009), which indicate that accumulation in the intestinal wall can inhibit further transport of MCs into internal organs. The MC concentrations in the livers of the four fish species studied here were all relatively low, which contradicts the results of previous studies (Kankaanpää et al, 2005;Li et al, 2004;Malbrouck et al, 2003;Xie et al, 2005). The liver is an important detoxification organ, and bile plays an important role in the elimination and recirculation of excess MCs from the fish liver (Tencalla and Dietrich, 1997).…”
Section: Discussioncontrasting
confidence: 97%
“…However, other authors found MC concentrations in phytoplanktivorous fishes (Zhang et al, 2009) higher than those reported by Xie et al (2005). No significant difference was observed for the MC concentrations between phytoplanktivorous and omnivorous fishes (p N 0.05) in the present Table 3 Correlations between MCs in variety organs of study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Little information is available on the toxic effects of MCs in phytoplanktivorous fishes that are more frequently exposed to cyanobacterial toxins under natural conditions because of habitat and feeding mode. It has been reported that silver carp (Hypophthalmichthys molitrix) accumulates MCs in intestine, blood, liver, kidney and muscle like other freshwater fish [10] , at levels above the tolerable daily intake (TDI) of 0.04 μg/kg body weight (BW) per day proposed by WHO as a provisional guideline value [11] . This is of great concern for public health because chronic ingestion of trace amounts of MCs (MC-LR in particular) in food and drinking water has a considerable potential to promote cancer [2] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 80 structural analogs of MCs have been identified, and microcystin-RR (MC-RR) is one of the dominant variants in cyanobacterial blooms in lakes of China [3,4]. MCs primarily act as hepatotoxins because the liver is the target organ in various animals.…”
Section: Introductionmentioning
confidence: 99%